Anodic oxidation by electrical power pulses for alachlor degradation - Zouaoui, Fares (Environmental technology, 2025)
This article explores the benefits of electrochemical oxidation in pulsed mode, using potential, current, and power pulses. While potential and current pulse electrochemical technology has been previously studied for wastewater treatment, no study has included power pulses until now. The objective of this work is to highlight the advantages of power pulses by applying this pulse type to the electrochemical oxidation of a probe molecule, alachlor. For this aim, the influence of operating parameters and the comparison of the different pulse modes were investigated and compared to the results obtained with the electrochemical oxidation of alachlor in continuous mode. The study shows that the best results were obtained with the power pulse electrochemical oxidation with 100% alachlor degradation after 180 min and a mineralisation yield of 38.3% after 240 min. These results were better than those reported in the literature for treatments with continuous current input using platinum electrodes. This new technique could be an effective and efficient way to treat contaminated water and reduce the pressure on freshwater reserves